2018
DOI: 10.1007/s12517-018-3793-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of ASTER data and geochemical analyses for the exploration of gold at Samut area, South Eastern Desert of Egypt

Abstract: The present study investigates the use of ASTER and geochemical data in the exploration of new gold occurrences in altered granodiorite rocks at Samut area in the South Eastern Desert of Egypt. The mapping approach developed and applied in this study integrates image ASTER and field data sets to produce a map showing the alteration zones within granitoid rocks in the Samut area. Due to the differences in hydrothermal mineral components as well as their intensities and influences on the surrounding rocks, vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…By combining ASTER spectral analysis with geochemical data from surface-collected samples, Salem et al [137] were able to validate alteration zones detected on the remote sensing data, and strengthen the association of ASTER-defined targets with potential gold deposits. Abdelnasser [138] and Salem et al [139], in separate studies, reported similar ASTER-plus-geochemistry studies at the Atud gold deposit and the Samut area, respectively. By establishing a physical tie between alteration and gold occurrence, an exploration strategy using only remote sensing data was formulated.…”
Section: Aster Data Applied To Gold Explorationmentioning
confidence: 65%
“…By combining ASTER spectral analysis with geochemical data from surface-collected samples, Salem et al [137] were able to validate alteration zones detected on the remote sensing data, and strengthen the association of ASTER-defined targets with potential gold deposits. Abdelnasser [138] and Salem et al [139], in separate studies, reported similar ASTER-plus-geochemistry studies at the Atud gold deposit and the Samut area, respectively. By establishing a physical tie between alteration and gold occurrence, an exploration strategy using only remote sensing data was formulated.…”
Section: Aster Data Applied To Gold Explorationmentioning
confidence: 65%
“…Many authors have been used ASTER data to map the promised alteration zones for mineral potentiality e.g. ; (Salem et al, 2016(Salem et al, , 2018.…”
Section: Methodsmentioning
confidence: 99%
“…[10] used of Aster data and geochemical analysis for the exploration of gold at Samut (Samut) area, South Eastern Desert, Egypt. Salem "et al". 2018 [11] used of Aster data and geochemical analysis for the exploration of gold at Samut (Samut) area, South Eastern Desert, Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Salem "et al". 2018 [11] used of Aster data and geochemical analysis for the exploration of gold at Samut (Samut) area, South Eastern Desert, Egypt. The concept of the band rationing technique was widely used in different areas (Rowan et [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%